2022
DOI: 10.3390/life12030351
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ceramide Glycosylation Enhances Cisplatin Sensitivity in Cholangiocarcinoma by Limiting the Activation of the ERK Signaling Pathway

Abstract: Cholangiocarcinoma (CCA) is an aggressive tumor of the biliary epithelium with poor survival that shows limited response to conventional chemotherapy. Increased expression of glucosylceramide synthase (GCS) contributes to drug resistance and the progression of various cancers; the expression profiles of GCS (UGCG) and the genes for glucocerebrosidases 1, 2, and 3 (GBA1, GBA2, and GBA3) were therefore studied in CCA. The biological functions of GCS for cell proliferation and cisplatin sensitivity in CCA were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…UVM patients were divided into high and low risk groups according to the median risk score, and significant prognostic differences were found between the two groups. In other reports, non-lysosomal β-glucosidase (GBA2) hydrolyzed GlcCer to release ceramide and glucose on the cytoplasmic side of ER and golgi membrane, potentially affecting tumor drug resistance ( 58 , 59 ). Alpha-galactosidase (GLA) has long been considered a key link in Fabry’s disease ( 60 ), but has rarely been studied in tumors, which seems to provide a way to link Fabry’s disease and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…UVM patients were divided into high and low risk groups according to the median risk score, and significant prognostic differences were found between the two groups. In other reports, non-lysosomal β-glucosidase (GBA2) hydrolyzed GlcCer to release ceramide and glucose on the cytoplasmic side of ER and golgi membrane, potentially affecting tumor drug resistance ( 58 , 59 ). Alpha-galactosidase (GLA) has long been considered a key link in Fabry’s disease ( 60 ), but has rarely been studied in tumors, which seems to provide a way to link Fabry’s disease and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, since GBA2 can cleave glucosylceramide to produce ceramides, ceramides have been shown to act as tumor suppressors in a variety of tumors ( 35 37 ). GBA2 also has been shown to function as a tumor suppressor in melanoma cells and cholangiocarcinoma ( 38 , 39 ). Meanwhile, based on the role of GBA2 in inflammatory response ( 40 ), we analyzed the relationship between GBA2 and immune cell infiltration in the tumor microenvironment, and found that GBA2 was positively correlated with B cells, but negatively correlated with M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%